Treinadoras no futebol de mulheres no Brasil: trajetórias em construção - Santos, Marilia Baldoino [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Historically, women face greater difficulty in entering the job market, since there is still a culture in which they are recognized as responsible for motherhood and home care, and must, if not exclusively, combine this function with other works). The process of conquering women's spaces so that women can enjoy rights similar to those of men has been built with a lot of toil. This is no different in the sports scene. In the case of women's football, Brazil has gone through several phases, from its development in the mid-twentieth century, its ban in the 1940s and its resumption only in the late 1970s, which helps us understand the great difference in comparison with football played by men, both in terms of leisure and high performance This scenario brings significant influences in several fields, among them, the training and performance of football coaches. In this sense, this study aimed to identify and analyze the perspectives of women on the construction of their trajectories as coaches in women's soccer in Brazil. The investigation, of a qualitative nature, made use of the semi-structured interview as a collection technique, involving five elite women's soccer coaches who were working in Brazil in the year 2021. The results showed that all of them had a sporting beginning as players and, after the end of their careers, they saw in the coaching profession a continuity within the sport. Among the challenges experienced in this journey, the following were highlighted: problems related to machismo, lack of adequate structure, lack of support from clubs; salary problems. Despite these confrontations, they see a future of appreciation for the profession. These women revealed a combination of resistance/persistence with hope, pointing out that in this field of disputes, fueled by prejudice, there is no conquest without a struggle.

As mulheres enfrentam, historicamente, uma maior dificuldade para se inserir no mercado de trabalho, uma vez que ainda há uma cultura na qual elas são reconhecidas como responsáveis pela maternidade e pelos cuidados com a casa, devendo, quando não exclusivamente, conjugar essa função com outro(s) trabalho(s). O processo de conquista dos espaços femininos para que as mulheres possam usufruir de direitos semelhantes aos dos homens vem se construído com muita labuta. Isso não é diferente no cenário esportivo. No caso do futebol de mulheres, o Brasil passou por diversas fases, desde o seu desenvolvimento, em meados do século XX, a sua proibição na década de 1940 e sua retomada apenas no fim dos anos 1970, o que nos ajuda a compreender a grande diferença na comparação com o futebol praticado pelos homens, tanto no âmbito do lazer quanto no alto rendimento Tal cenário traz significativas influências em vários campos, dentre eles, o da formação e atuação de treinadoras de futebol. Nesse sentido, esse estudo teve como objetivo identificar e analisar as perspectivas de mulheres sobre a construção de suas trajetórias como treinadoras no futebol de mulheres no Brasil. A investigação, de caráter qualitativo, fez uso da entrevista semiestruturada como técnica de coleta, envolvendo cinco treinadoras da elite do futebol de mulheres que estavam atuando no Brasil no ano de 2021. Os resultados apontaram que todas elas tiveram um início esportivo como jogadoras e, após o fim de suas carreiras, viram na profissão de treinadora uma continuidade dentro do esporte. Dentre os desafios vividos neste percurso foram destacados: problemas relacionados ao machismo, falta de estrutura adequada, falta de apoio por parte dos clubes; problemas salariais. Apesar destes enfrentamentos elas veem um futuro de valorização para a profissão. Estas mulheres revelaram uma conjugação de resistência/persistência com esperança, assinalando que neste campo de disputas, alimentado pelo preconceito, não há conquista sem luta.
Women's soccer coaches in Brazil: trajectories under construction
Keywords: Soccer; Woman; Futebol; Mulheres